Application of Education Law as Determinant of Principals’ Personnel Management Effectiveness of in Public Secondary Schools in IMO State - Israel C. Oparaji; Martha-Rose Ifeoma Uwaezuoke; Chinenye Eucharia Okonkwo (CV. Samuel Manurung and Co, 2024)
This study examined the application of education law as determinant of principals’ personnel management effectiveness in public secondary schools in Imo State. Two research questions and two hypotheses guided the study. The descriptive survey research design was adopted for the study. The population of the study comprises 5,286 teachers of public secondary schools in Imo State. Random sampling technique was used to select 134 (48 males and 86 females) principals while multistage random sampling technique was used to draw 529 teachers made up of 89 males and 440 females. The instrument was structured by the researchers and named “Application Education Law as Determinant of Principals’ Personnel Management Effectiveness Questionnaire” (AELDPPMEQ). The instrument was validated by three experts, two from the Department of Educational Management and policy while one from the Department of Educational Foundation. The reliability of the instrument was obtained through Pearson Moment Correlation Coefficient with index value of 0.82 which was considered high enough for the study. Mean and standard deviation were used to answer the research questions while t-test was used test the hypotheses at 0.05 level of significant. The finding of the study among others was that principals of schools in the study area to a high extent apply education law in their personnel management practices. It was then recommended that government should encourage principals to apply education law to make for their personnel management effectiveness.